Travail, emploi et douance - Yann-Gaël Jaffré; Laurence Dulon; Steven Verbeek (Perspectives Interdisciplinaires sur le Travail et la Santé)
Interest in the place accorded to gifted adults in our society and the socio-occupational integration difficulties they have to deal with has grown over the last few years. Despite their intelligence, gifted people have certain vulnerabilities and do not always enjoy working conditions that would allow them to develop to their full potential. However, public policies, be they European or national, are paying more attention to their place in socio-productive organizations. Given the importance of promoting diversity and quality of work life, a collective investment in this issue would undoubtedly be beneficial to society and allow it to better integrate the myriad resources of human intelligence.